COMPOUND WORDS THAT OCCUR DURING THE GLOBAL PANDEMIC COVID-19: A MORPHOSEMANTIC STUDY - Ervina CM Simatupang; Ida Zuraida Supri (University of Kuningan, 2020)
This study aims to analyse and examine closely the category of compound words that occur during the global pandemic COVID-19 and their type of meaning. The method used in carrying out the study was a descriptive analysis method. The data used were taken from the official website of the World Health Organization (WHO) in the ‘Your Questions Answered’ section. The results demonstrated that there are two types of compound word found, namely compound nouns (67%) and compound verbs (33%). Besides, there are three types of meaning found, namely literal meaning (50%), semi-idiomatic meaning (33%), and idiomatic meaning (17%). Furthermore, in the category of compound nouns, the types of meaning that occur are literal meaning (50%), semi-idiomatic meaning (25%), and idiomatic meaning (25%). Meanwhile, the types of meaning that appear in the category of compound verbs are literal meaning (50%) and semi-idiomatic meaning (50%).